Can One Speak of the Nature or Essence of a Woman? - Baranowska, Maria Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The issue of the nature or essence of a woman is a very practical problem for Edith Stein. The upbringing and education of women should be based on knowledge of a woman’s nature and her life's vocation. Edith Stein makes use of science – particularly psychology – literature, common knowledge, and above all, philosophy and the Biblical message of faith. Women and men have a common basic vocation, to be an image of God, and both need to develop their talents, capabilities and powers in a full and harmonious manner. This development comprises three levels: humanity, femininity or masculinity and their singular individuality. Edith Stein’s approach to the specific character of a woman’s nature is holistic, concrete and personal, based on a maternal and caring attitude, and above  all on the desire to love and be loved. Edith Stein describes nature or essence from the perspective of action. Like the essence of things, the individual specificity of each person is not fully knowable; it can be known only intuitively. One might formulate the hypothesis that femininity is a simple and irreducible quality that affects the whole structure of a person.